Layout optimisation of fishbone robotic mobile fulfilment system. (7th October 2022) - Wang, Yanyan; Man, Rongjun; Zhao, Wanmeng
Robotic mobile fulfilment system (RMFS) heavily influences all traditional scheduling problems when operating a warehouse. Rack layout affects the efficiency of inbound and outbound and the utilisation ratio of storage. This paper focuses on analysing the compatibility between fishbone storage layout and RMFS and its equipment kinetic characteristics, such as movement velocity and acceleration. By building the equipment kinetic functions and subsequently simulating various fishbone storage layout solutions features by length-to-width ratio, storage volume, and rack size, this research analyses the relationship between inbound/outbound efficiency and warehouse space utilisation. The applicability range of fishbone rack layout is obtained by comparing conventional layout with different rack size. Meanwhile, energy consumption is of great significance to reduce warehousing operating costs and improve operational efficiency. Therefore, the impacts on inbound/outbound efficiency and energy consumption from velocity and acceleration are investigated. Results show that optimal velocity ranges between 1.5 m/s and 2 m/s and the optimal acceleration ranges between 0.2 m/s 2 and 0.25 m/s 2 . Too high acceleration or velocity is easy to cause congestion and deadlock, which is not easy to schedule. Overall, this research provides decision support for parts-to-picker system design. [Submitted: 19 March 2021; Accepted: 22 September 2021]